2019
DOI: 10.1371/journal.pone.0226211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotional information from eyes on empathy for pain: A subliminal ERP study

Abstract: Facial expressions are deeply tied to empathy, which plays an important role during social communication. The eye region is effective at conveying facial expressions, especially fear and sadness emotions. Further, it was proved that subliminal stimuli could impact human behavior. This research aimed to explore the effect of subliminal sad, fearful and neutral emotions conveyed by the eye region on a viewer’s empathy for pain using event-related potentials (ERP). The experiment used an emotional priming paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…In an auditory Go/No-Go task, Barry et al (2007) found that a single oral dose of caffeine (250 mg) resulted in focal rather than global increases in P1, P2, and P3b amplitudes to Go stimuli with no changes in latency, suggesting that caffeine differentially improves aspects of processing related to response production and task performance (Barry et al, 2007). Within the visual Go/NoGo paradigm, ERP studies have suggested that the N2 component reflects stimulus perception (Dulinskas and Ruksenas, 2019;Song et al, 2019), cognitive control, and response inhibition (Magnuson et al, 2019;Quaglia et al, 2019). P300 is the largest positive-going peak amplitude of the waveform within a time window of 300-400 ms and is considered to represent the allocation of attentional resources to rare salient stimuli (Cote et al, 2001;Marhöfer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In an auditory Go/No-Go task, Barry et al (2007) found that a single oral dose of caffeine (250 mg) resulted in focal rather than global increases in P1, P2, and P3b amplitudes to Go stimuli with no changes in latency, suggesting that caffeine differentially improves aspects of processing related to response production and task performance (Barry et al, 2007). Within the visual Go/NoGo paradigm, ERP studies have suggested that the N2 component reflects stimulus perception (Dulinskas and Ruksenas, 2019;Song et al, 2019), cognitive control, and response inhibition (Magnuson et al, 2019;Quaglia et al, 2019). P300 is the largest positive-going peak amplitude of the waveform within a time window of 300-400 ms and is considered to represent the allocation of attentional resources to rare salient stimuli (Cote et al, 2001;Marhöfer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese people have typical oriental emotions that are exhibited with subjective-will in an implicit way rather than in the open way. The fear expressions on faces of Chinese people even reacted more slowly than other negative expressions when depicting pain even after the sad emotion priming [47]. The self-reserved habit to show scared expressions can also be extended to the Yonsei database from a Korean population [45].…”
Section: Discussionmentioning
confidence: 95%
“…Chinese people, characteristic of how Asians typically display emotions, show emotions implicitly rather than explicitly. For example, Chinese people’s expression of fear forms more slowly than other negative expressions when depicting pain, even after sad emotions priming [ 51 ]. Chinese people’s tendency to suppress expressions of fear by adopting a self-reserved character can be extended to the Korean population’s Yonsei database [ 47 ].…”
Section: Discussionmentioning
confidence: 99%